A methodological proposal for the technical conception of microgrids (2019)
This paper introduces a methodology for the technical conception of microgrids. It takes into account aspects such as the topological survey of the medium power electrical system, the preselection of renewable sources technologies, the prioritisation of the electrical demand, the localization, dimensioning and operative strategies of the distributed generators, the components model and the microgrid evaluation. This methodology proposes the use of a multi-criteria analysis technique for the prioritisation of the demand and the stability index of (SI) voltage for the location of distributed generators in the microgrid. In this work the computational tool for the power system analysis Neplan® was used for the components modeling and evaluation of the microgrid performance through the IREG voltage regulation index and the optimal power management of the microgrid’s generation units.